Motywacja w procesie tworzenia chrematonimii marketingowej - Gałkowski, Artur (Poznańskie Spotkania Językoznawcze, 2014)
The paper presents different notions regarding the general functioning of motivation during the process of formation of proper names. Making use of the specific methodological key, the analysis moves to the marketing chrematonymy and concentrates on it. The author distinguishes several types of motivation in the marketing chrematonymy area, including the conceptual motivation, the interonomastic motivation, the associative-connotative motivation, the formal-creative motivation and finally, the cultural motivation, which plays the principal role in this statement.